Examining Temporary Migration as a Solution to the Lean Season - Alikiah Barclay; Ben Soltoff; Chijioke Onyekwelu; Chris Martin; Mushfiq Mobarak (Faculty of Economics and Business, Hasanuddin University, 2017)
Our research in Indonesia took as its focus the concept of the lean season, that is, predictable times of scarcity which contribute to large drop offs in productivity, consumption and caloric intake for an affected region and its people. For this research, we partnered with students from Universitas Hasanuddin (UnHas) in Makassar to leverage their knowledge of the local language and broader cultural context. They proved to be invaluable colleagues as we met with the various constituencies across South Sulawesi. We conducted first-person interviews with village leaders, as well as agricultural workers and city employers. Through these formal interactions – and impromptu meetings and conversations too – we were able to get a sense of the viability of a temporary migration scheme like the ones implemented in Bangladesh and Timor by Dr. Mobarak and his team. We made serious effort to embark on lines of questioning which were open-ended instead of suggestive and, when appropriate and possible, conducted our interviews with individuals as opposed to groups to ward off collectivist thinking. In particular, our questions were meant to illuminate the lived experience of locals around four broad areas of concern: the agricultural calendar, coping mechanisms, migration history and employer insights. The coming pages spell out our findings.